HUBUNGAN PENGETAHUAN TENTANG HIV/AIDS DAN SIKAP PEKERJA SEKS KOMERSIAL TERHADAP PERILAKU DALAM MENGIKUTI VCT DI SURAKARTA - Kumalasari, Mei Lina Fitri (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2017)
[The prevalence of HIV/AIDS is always increasing. To reduce the incidence of HIV/AIDS figures, the Government set the strategy through early detection and counselling voluntarily, one of which is a service of the Voluntary Counseling and Testing (VCT). The behavior follow VCT is influenced by several factors, such as knowledge and attitudes. The purpose of this research is to analyze the relationship of knowledge about HIV/AIDS and attitudes toward the Behavior of commercial sex workers in following VCT In Surakarta. This research is research observational analytic approach with cross sectional and implemented in the localization of the region of Surakarta. Do test validity and reliability with a total sample of 30. Samples of research a number of 105 PSK with accidental sampling sampling techniques. The data were analyzed using poisson regression with robust variance with STATA SE version 12.0. The results showed there was a significant relationship between knowledge about HIV/AIDS and the attitude of PSK with behavior follow.] Keywords: knowledge, attitude and utilization of VCT